A rare presentation of neuroendocrine prostate carcinoma in young adult: A case report - giddi, mauryakrishna; Parashar, Eresh; nigam, neha; Dey, Treshita (Indian Journal of Case Reports, 2026)
Neuroendocrine prostate carcinoma (NEPC) is an aggressive malignancy characterized by a poor prognosis and distinct clinical and histopathological features compared with the more common prostatic adenocarcinoma. We report a case of a 37-year-old male who presented with lower urinary tract symptoms and was initially managed as having high-grade invasive urothelial carcinoma of the bladder, but was ultimately diagnosed with high-grade neuroendocrine carcinoma of the prostate. This case highlights the diagnostic complexity arising from overlapping clinical and imaging findings with bladder carcinoma and underscores the importance of histopathological and immunohistochemical evaluation for accurate diagnosis. Despite aggressive therapy, the disease followed a rapid course, emphasizing the need for further research into more effective treatment strategies.